Identity and Image of A Private University After Incorporation Process: Students' Perception - Damasceno, Tamara Almeida (International Journal of Scientific Research and Management (IJSRM), 2025)
Intense processes of mergers and acquisitions were noticed in the Brazilian context of Private Higher Education Institutions from the 2000s onwards. These manifestations triggered new conceptions and forms of management of these organizations and called into question the identity and image previously constructed with the actors in the process (Stakeholder) in the context of these institutions. What is perceived nowadays is a great race for competitive market advantages. This study analyzed the perception of students from 42 courses at a Private University that went through an incorporation process and was structured from the perspective of analyzing the Theory of Identity and Organizational Image. The results showed that the perceived impact in relation to identity and image was guided by two dimensions – the immediate and the one under reconstruction –, considering that the longitudinal research indicated differences between the initial moment of incorporation and the results obtained in the last phase of the research. These differences demonstrated conflicts in relation to identity and image at the initial moment of incorporation and, as strategic and institutional actions began to be implemented, it was possible to perceive new perspectives in relation to identity and image being constructed by the actors and their views on the organization.